Juridical Review of The Service Bureau in Assistance in The Management of Motor Vehicle Tax Payments - Suisno; Kasumawati, Devi; Muljono, Bambang Eko; Ramadhoni, Akhmad Syariffudin (Jurnal Independent, 2026)
This study discusses the legality of service bureaus in assisting with motor vehicle tax administration and the potential for fraudulent practices that may occur in their implementation. The use of service bureaus by the public to facilitate the administrative process of motor vehicle tax payments is becoming increasingly common. However, this trend has not been matched by clear legal regulations regarding the status and operations of such service bureaus. The purpose of this study is to examine the legal status of service bureaus from the perspective of Indonesian legislation and to identify potential legal violations committed by certain individuals within these bureaus. The research method used is Normative Legal Research, a method aimed at examining laws and regulations, legal doctrines, and legal concepts related to the issues under study. Normative legal research was chosen because the primary focus of this study is the analysis of legal rules concerning motor vehicle taxation and the legality of service bureaus that assist with the payment process. There is a need for more explicit and specific legal regulation to prevent abuse and to provide legal certainty in the use of service bureaus related to motor vehicle tax administration.